Silence and Sameness in the Norwegian Church Abroad - Iversen, Lars Laird (2021)
Employees of the Norwegian Church Abroad (NCA) avoid discussing politics. Understanding why increases sociological understanding of how everyday and nonextreme forms of religion may contribute to everyday and nonextreme forms of national feeling. This article leverages insights from studying the NCA in order to contribute to the sociological literature on everyday nationalism and religion. It does this by illustrating how the microsociological strategies of silence and avoidance contribute to imagined sameness. This increases our understanding of how everyday belonging draws resources from both nation and religion. Furthermore, it highlights the interactions between religion and nation as both resources for belonging and grounds for difference. The findings are based on interviews with 32 employees in six churches in the United States, and supporting observations.
Keywords: Avoidance; Silence; imagined sameness; everyday nationalism; Everyday Religion; Norwegian Church Abroad